THE EFFECT OF WORKLOAD AND WORK ENVIRONMENT ON JOB BURNOUT (Case Study at Eye Hospital Sulawesi Utara) - Dondokambey, Zaneta Devina Viona; Saerang, David P.E; Pandowo, Merinda Ch. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Job burnout is a high risk for all organizations in terms of employee well-being, business and productivity. Workload and work environment are considered as two of the organizational factors that can influence job burnout in healthcare workers. This study aims to examine the effect of workload and work environment on job burnout. This research is causal type of research with quantitative approach.. The primary data gathered in form of questionnaire that consists of 30 item of questions representing the indicators by using likert-scale. The investigated population in this study is the employee of Eye Hospital Sulawesi Utara while, the sample size are 87 respondents. Data analysis used Multiple Linear Regression by SPSS 23 statistical software. Data collected are valid and reliable. The findings reveal that the value of the coefficient determination test is 78.5 percent. Moreover, the results show that the workload and work environment variables simultaneously influence job burnout, workload has a partial effect on job burnout, whereas work environment has no partial effect on job burnout. This study suggests that decision makers in this hospital should avoid giving extra workload or unnecessary tasks and consider giving more incentive to ensure employee well-being. Keywords: workload, work environment, job burnout